A comprehensive model of colour appearance for related and unrelated colours of varying size viewed under mesopic to photopic conditions. Issue 3 (21st August 2016) - Wei, Shou Ting; Luo, Ming Ronnier; Xiao, Kaida; Pointer, Michael
Abstract: CIE has recommended two previous appearance models, CIECAM97s and CIECAM02. However, these models are unable to predict the appearance of a comprehensive range of colours. The purpose of this study is to describe a new, comprehensive colour appearance model, which can be used to predict the appearance of colours under various viewing conditions that include a range of stimulus sizes, levels of illumination that range from scotopic through to photopic, and related and unrelated stimuli. In addition, the model has a uniform colour space that provides a colour‐difference formula in terms of colour appearance parameters. © 2016 Wiley Periodicals, Inc. Col Res Appl, 42, 293–304, 2017